Pengaruh Aktivitas Membuat Boneka Jerami Terhadap Perkembangan Kreativitas dan Sosial Emosional Anak Kelompok B di TK Muslimat NU 02 dan TK PGRI 01 Kabupaten Lumajang - Laili Devi Agustin (Universitas Trunojoyo Madura, 2017)
The results of the initial observations indicate that the interaction and creativity of children Group B is still low. In fact, children should be encouraged to develop an interest in learning everything. Therefore, the researchers examined the effect of treatment on Effect of Straw Puppet Making Activity Against Creativity and Social Emotional Development of Children in Kindergarten Group B Muslimat NU 02 and TK PGRI 01 Lumajang.formulation of the problem of this study is whether the activity of making straw dolls affect the social emotional development of children's creativity and group B. This study aimed to determine the effect of the activity of making straw dolls influential the social emotional development of children's creativity and group B